2015
DOI: 10.1515/jcim-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and anti-lipoperoxidative activities of bark extracts of Xylopia aethiopica against ion-mediated toxicity on liver homogenates

Abstract: Reactive oxygen species (ROS), products of normal cell metabolism may cause damage to biological macromolecules leading to severe health threats when they are present in high concentrations. Aromatic plants contain phytochemicals rich of antioxidants that prevent oxidant formation or scavenge oxidants produced under oxidative stress conditions. In the present study, we investigated the free radical scavenging effects, the antioxidant and ion toxicity preventive effect of Xylopia aethiopica (X. aethiopica), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…That molecule can be of enzymatic origins such as the SOD, catalase, and peroxidase [ 10 , 12 ]. This study has shown a significant variation of the activity of antioxidant enzymes from one organ to another corroborating previous authors who demonstrated the disparities in the antioxidant response between different vital organs [ 14 ]. The variation of the concentration of antioxidant enzymes in biological samples has been used in a diversity of study as a marker of oxidative stress [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…That molecule can be of enzymatic origins such as the SOD, catalase, and peroxidase [ 10 , 12 ]. This study has shown a significant variation of the activity of antioxidant enzymes from one organ to another corroborating previous authors who demonstrated the disparities in the antioxidant response between different vital organs [ 14 ]. The variation of the concentration of antioxidant enzymes in biological samples has been used in a diversity of study as a marker of oxidative stress [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…The mixture was then centrifuged at 5000 rpm for 30 min [ 9 ]. The supernatant was then collected and kept in a fridge at 4°C for further experiments [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenolic compounds, widely distributed in plants, are known to have multiple biological effects such as anti-inflammatory, antidiabetic, antioxidant, and hepatoprotective [23, 24]. Recently, more attention has been given to plants which contain this class of compounds, with more emphasis on those used in the human diet [25, 26]. The fruit of T. tetraptera is a spice used as a condiment in Cameroon.…”
Section: Discussionmentioning
confidence: 99%